2015
DOI: 10.1002/pc.23859
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on rheological and mechanical behavior of poly(3‐Hydroxybutyrate)/cellulose nanocrystal based nanobiocomposites

Abstract: The work focused on the formation of percolation network by cellulose nanocrystals (CNCs) in poly(3-hydroxybutyrate) (PHB) matrix, which affects the rheological and mechanical properties of the polymer. Rheological investigations revealed the formation of a percolation network in the fabricated PHB/CNC films with a percolation threshold at a CNC loading of approximately 2 wt%. This observation was further confirmed by both mechanical analysis and modeling studies using Halpin-Kardos and Ouali models. The tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…This increase in properties has been reported to be associated with the efficient dispersion of CNCs, which allows for a high interfacial adhesion between them and the matrix. In agreement with these results, Bhardwaj et al [10,29] have reported an increase in E (from 1321 MPa to 1412 MPa) and σ UTS (from 36 MPa ± 1.4 MPa to 45 MPa ± 1.8 MPa) with a 5 wt % addition of CNCs. In addition, their work concludes that concentrations as low as 2 wt % of CNCs in the PHB matrix could lead to higher improvements in mechanical properties as this allows for better dispersion and intercalation reinforcement into the PHB matrix.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This increase in properties has been reported to be associated with the efficient dispersion of CNCs, which allows for a high interfacial adhesion between them and the matrix. In agreement with these results, Bhardwaj et al [10,29] have reported an increase in E (from 1321 MPa to 1412 MPa) and σ UTS (from 36 MPa ± 1.4 MPa to 45 MPa ± 1.8 MPa) with a 5 wt % addition of CNCs. In addition, their work concludes that concentrations as low as 2 wt % of CNCs in the PHB matrix could lead to higher improvements in mechanical properties as this allows for better dispersion and intercalation reinforcement into the PHB matrix.…”
Section: Discussionsupporting
confidence: 73%
“…Cellulose nanocrystals (CNCs)—which can be obtained from an assortment of biomass products such as coconut fibers and wood—have been previously used as reinforcing agents for biopolymers such as PHB, PLA and poly (vinyl alcohol) (PVA), improving their mechanical properties [22,28]. These materials are highly abundant in nature, eco-friendly, and renewable [22,28,29]. Arrieta et al [22] investigated hot-pressed PLA and PLA-PHB blended films (3:1 ratio) with the addition of 5 wt % pristine CNCs material [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previously reported studies 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 (Table S2). For the perpendicularly oriented samples, the percentage crystallinity improved by ~4% at 3 wt% MGCNC loading.…”
Section: Anisotropic Thermal Properties Of Pla Based Mgcncs Nanocompomentioning
confidence: 74%
“…Other researchers [50] stated that under higher CNCs loading, CNCs begin to aggregate in the form of clusters on the surface of the polymer, and the side effects on mechanical properties are more significant.…”
Section: Effect Of Nanocellulose On the Mechanical Properties Of Phbmentioning
confidence: 99%